Metode Penelitian Analisis Semiotik Media Sosial - Pranindita Dwi Fadhila; Chintya Almira; Aldi Priatmana (Dakwatussifa: Journal of Da'wah and Communication, 2022)
Semiotics or semiotics are terms that refer to the same science. Semiotics is commonly used by American scholars, although the term semiotics is more commonly used in Europe. Semiotics comes from the Greek word semeion, which means 'sign', or the English sign, which means 'signal'. Semiotics is known as a science that studies sign language systems such as languages, codes, signals, and human language. Semiotics is the science of symbols. To be able to read and interpret these symbols, we need "language". Meaning is formed through a structured system of linguistic differences. Meaning is generated through the process of selecting and combining symbols around two axes, the syntagmatic axis (linear, for example sentences) and the paradigm axis (the arena of symbols such as synonyms) which are arranged in a marking system. This symbol consists of a signifier (medium) and a symbol (meaning) (Saussure, 1960). The purpose of semiotic analysis is to find the meaning of symbols, including what is hidden behind them (text, advertisements, news). Keywords: history of semiotics, semiotics Roland Barthes, understanding of semiotics, semiotic figures, development of semiotics.